Mycobacterium neoaurum bacteremia in a hemodialysis patient - Becker, Marissa L (Pulsus Group Inc, 2003)
Bacteremia due to Mycobacterium neoaurum, a rapidly growing mycobacterium, is described in a diabetic woman on hemodialysis. This is the first reported case of M neoaurum bacteremia in Canada. The organism initially grew on standard BacT/Alert SA aerobic blood cultures, and was subsequently positively identified using 16S rRNA sequence analysis. The present case serves to reinforce the need for a high index of clinical suspicion of infections caused by unusual microorganisms in the context of an immunocompromised host